2015
DOI: 10.1111/wrr.12358
|View full text |Cite
|
Sign up to set email alerts
|

Negative pressure and nanocrystalline silver dressings for nonhealing ulcer: A randomized pilot study

Abstract: Chronic wounds have a high prevalence and wound care, treatment, and prevention consume large quantities of resources. Chronic wounds are a growing challenge for clinicians. A prospective randomized pilot study was conducted to assess the effectiveness in terms of reduction in area and safety of the combined use of negative-pressure wound therapy and nanocrystalline silver dressings as compared to negative pressure wound therapy (NPWT) alone in the management of outpatients with chronic wounds. A total of 17 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
1
0
3
Order By: Relevance
“…Study participants tolerated the dressing for the duration of the study. These findings are consistent with other studies of silver dressings for use in chronic wounds 3,24–30 . Previous systematic and scoping reviews have reported heterogeneity in wound healing outcomes within and between studies, and this is likely a factor in the current study 10,12,31 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Study participants tolerated the dressing for the duration of the study. These findings are consistent with other studies of silver dressings for use in chronic wounds 3,24–30 . Previous systematic and scoping reviews have reported heterogeneity in wound healing outcomes within and between studies, and this is likely a factor in the current study 10,12,31 .…”
Section: Discussionsupporting
confidence: 90%
“…These findings are consistent with other studies of silver dressings for use in chronic wounds. 3,[24][25][26][27][28][29][30] Previous systematic and scoping reviews have reported heterogeneity in wound healing outcomes within and between studies, and this is likely a factor in the current study. 10,12,31 However, it remains important to conduct systematic clinical studies to evaluate new products for wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…7 A associação da TFPN de uso único com a cobertura de tela de poliéster flexível com prata nanocristalina reduziu a carga bacteriana e demostrou uma combinação segura e eficaz. 8 Este trabalho tem como objetivo demonstrar a utilização da Terapia de Ferida por Pressão Negativa de Uso Único em domicílio para proporcionar o fechamento por segunda intenção de deiscência cirúrgica de osteossíntese maleolar.…”
Section: Introductionunclassified
“…La velocidad de reducción del tamaño de la herida en pacientes tratados con terapia negativa y plata frente a terapia negativa fue similar para ambos grupos de tratamiento, aunque ligeramente superior en el grupo combinado TPN-Ag (1,78 cm 2 /semana) frente al grupo control TPN aislada (1,63 cm 2 /semana) Solo se encontraron diferencias estadísticamente significativas de esta disminución entre las semanas 3 y 6 para el grupo con plata (p=0,028) 291 .Esto nos ayuda a comprender el beneficio de la plata en heridas crónicas, donde se ve que aceleraría la epitelización.…”
Section: La Citotoxicidad De La Plataunclassified
“…En nuestro trabajo no valoramos la absorción de plata a nivel sistémico, sin embargo, en otro estudio realizado por nosotros, en el que se valoró la toxicidad de apósitos de plata usados en ulceras crónicas donde se añadió terapia de presión negativa, no se evidenciaron niveles séricos tóxicos del ion plata ni a las 3 ni a las 6 semanas de tratamiento 291 .…”
Section: Infección Y Efectos Adversosunclassified